Increasing Quail Egg Hatching Production with 2 Sliding Rack Hatching Machine with temperature control and motor drive using Ardurino Uno Microcontroller - Adriansyah; Nusyirwan; Fajar Pradana; Fharel Abdillah; sumiati, Ruzita (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2024)
This study aims to design and develop a quail egg incubator utilizing an Arduino Uno microcontroller to regulate temperature and control the egg-turning motor. The incubation process requires precise environmental conditions, particularly consistent temperature and egg rotation, to ensure optimal hatching success. The Arduino Uno system is integrated with temperature sensors and a motor driver to automate these essential functions. The developed incubator was tested to monitor the system's stability and its ability to maintain the required incubation parameters. The results indicate that the automated control system effectively maintains the optimal temperature and performs egg rotation, contributing to improved hatchability rates. This research provides a cost-effective and accessible solution for small-scale quail egg incubation